Very low mass stellar and substellar companions to solar-like stars from MARVELS. IV. A candidate bronw dwarf or low-mass stellar companion HIP 67526 - Jiang, Peng (2013)
We report the discovery of a candidate brown dwarf (BD) or a very low mass stellar companion (MARVELS-5b) to the star HIP 67526 from the Multi-object Apache point observatory Radial Velocity Exoplanet Large-area Survey (MARVELS). The radial velocity curve for this object contains 31 epochs spread over 2.5 yr.OurKeplerian fit, using a Markov Chain Monte Carlo approach, reveals that the companion has an orbital period of 90.2695+0.0188 −0.0187 days, an eccentricity of 0.4375±0.0040, and a semi-amplitude of 2948.14+16.65 −16.55 m s−1. Using additional high-resolution spectroscopy, we find the host star has an effective temperature Teff = 6004 ± 34 K, a surface gravity log g (cgs) = 4.55 ± 0.17, and a metallicity [Fe/H] = +0.04 ± 0.06. The stellar mass and radius determined through the empirical relationship of Torres et al. yields 1.10±0.09M and 0.92±0.19R . The minimummass ofMARVELS- 5b is 65.0±2.9MJup, indicating that it is likely to be either a BD or a very low mass star, thus occupying a relatively sparsely populated region of the mass function of companions to solar-type stars. The distance to this system is 101 ± 10 pc from the astrometric measurements of Hipparcos. No stellar tertiary is detected in the high-contrast images taken by either FastCam lucky imaging or Keck adaptive optics imaging, ruling out any star with mass greater than 0.2 M at a separation larger than 40 AU.